Teachers Challenges and Strategies in Facing the Digitalization Era in Islamic Education in Madrasahs in West Java Region - Thursina, Fazrian; Rusdi, Muhammad (Westscience Press, 2024)
This study explores the challenges and strategies of teachers in madrasahs in the West Java region as they face the digitalization era in Islamic education. Utilizing a qualitative research design, semi-structured interviews were conducted with 15 teachers to gain in-depth insights into their experiences. Thematic analysis, conducted using NVivo software, revealed key challenges such as limited digital literacy, inadequate technological resources, and resistance to change due to traditional pedagogical values. To address these challenges, teachers employed strategies like peer collaboration, informal learning networks, and professional development initiatives. The findings emphasize the need for targeted digital literacy programs, improved technological infrastructure, and cultural shifts in educational practices to support the integration of digital tools in Islamic education. These insights can inform future policies and programs aimed at enhancing the effectiveness of Islamic education in the digital age.